A wind-tunnel study of the effect of turbulence on PM10 deposition onto vegetation. (June 2017) - Price, Timothy A.; Stoll, Rob; Veranth, John M.; Pardyjak, Eric R.
Abstract: The fraction of particles deposited from an airstream (deposition fraction) onto idealized substrates has been shown to be influenced by isotropic turbulence through increased deposition onto nonimpaction surfaces (Moran, S.M., Pardyjak, E.R., Veranth, J.M., 2013. Understanding the role of grid turbulence in enhancing PM10 deposition: scaling the Stokes number with R λ . Physics of Fluids 25, 115103). Here, we extend this by considering deposition onto realistic vegetative surfaces. Results from wind-tunnel deposition experiments conducted using nonvolatile particles and various types of artificial vegetation under grid-generated isotropic turbulence conditions are presented and compared with the previous idealized experiments. The nonimpaction-surface fraction of the total deposition is shown to scale with the Reynolds number and a new effective area parameterization is developed to account for inertial deposition onto nonimpaction surfaces. A combined formulation of the turbulent Stokes number and the effective deposition area are used to collapse the data. The results show that laminar impaction models dramatically under predict deposition for a given classical Stokes number. The new parameterization shows improved performance for deposition onto vegetation with the coefficient of determination ( r 2 ) increasing from 0.15 to 0.65 when accounting for turbulence and nonimpaction-surface deposition area.